(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Traumatic crush injury of the thumb can be devastating, often leading to poor functional outcomes. Various reconstruction options exist, dependent on surgical expertise. The Masquelet technique, well-established in the reconstruction of long bones in the lower limbs, has been scarcely reported for thumb injuries, with no documented cases in the Asia region. We present a case of a traumatic crush injury to the right thumb, initially managed with an antibiotic spacer, followed by reconstruction using a tricortical iliac graft in a two-stage Masquelet technique. This technique proved to be versatile, providing satisfactory functional and aesthetic outcomes.